The Effect of Combination of Video Feedback and Audience Feedback on Social Anxiety: Preliminary Findings. (September 2015) - Chen, Junwen; Mak, Rebecca; Fujita, Satoko
Although video feedback (VF) is shown to improve appraisals of social performance in socially anxious individuals, its impact on state anxiety during a social situation is mixed. The current study investigated the effect of combined video feedback and audience feedback (AF) on self-perceptions of performance and bodily sensations as well as state anxiety pertaining to a speech task. Forty-one socially anxious students were randomly allocated to combined video feedback with audience feedback (VF + AF), video feedback only (VF), audience feedback only (AF), or a control condition. Following a 3-min speech, participants in the VF + AF, VF, and AF conditions watched the videotape of their speech with cognitive preparation in the presence of three confederates who served as audience, and/or received feedback from the confederates, while the control group watched their videotaped speech without cognitive preparation. Both VF + AF and AF conditions improved distorted appraisal of performance and bodily sensations as well as state anxiety. The clinical implications of these findings are discussed.